Card-Collection Mechanics in Educational Location-Based AR Games: Transforming Learning Goals to Virtual Rewards - Vidal, Eric Cesar E, Jr (Archīum Ateneo, 2019)
Location-based AR (LBAR) games offer a potentially viable learning platform for history-related content, but the experience is impaired by player fatigue due to compulsory movement between real-world locations, causing engagement to drop as the length of the game increases. This paper proposes incorporating card-collection mechanics (virtual collectibles/achievements in contemporary games) into an existing history-related, narrative-based LBAR game, Igpaw: Loyola, to counter the effect of fatigue to player engagement while increasing their capacity to absorb educational content. Participants, divided into control and experimental batches, were tasked to play Igpaw: Loyola without and with the collection mechanic, respectively, under logged observation. Both versions of the game included required and optional locations. The control and experimental batches reported only minor differences in application usability, but a majority of the experimental batch visited the optional locations as opposed to none from the control batch. In the post-quiz, the experimental batch scored the same or better (on average and on each individual question) than the control batch. This leads to the conclusion that the card-collection mechanic significantly and positively impacts both the engagement and learning retention of players, and it is recommended for future LBAR games.